LncRNA H19 Regulates BMP2-Induced Hypertrophic Differentiation of Mesenchymal Stem Cells by Promoting Runx2 Phosphorylation - Dai, Guangming; Xiao, Haozhuo; Zhao, Chen; Chen, Hong; Liao, Junyi; Huang, Wei (Frontiers in Cell and Developmental Biology, 2020)
Objectives: BMP2 triggers hypertrophic differentiation followed after chondrogenic differentiation of mesenchymal stem cells (MSCs), which blocked the further application of BMP2 mediated cartilage tissue engineering. Here, we investigated the underlying mechanisms of BMP2 mediated hypertrophic differentiation of MSCs. Materials and methods: In vitro and in vivo chondrogenic differentiation models of MSCs were constructed. The expression of H19 in mouse limb was detected by FISH analysis. Transgenes BMP2, H19 silencing and overexpression were expressed by adenoviral vectors. Gene expression was determined by RT-qPCR, Western-blot and Immunohistochemistry. Correlations between H19 expressions and other parameters were calculated with Spearman’s correlation coefficients. The combination of H19 and Runx2 was identified by RIP analysis. Results: We identified H19 expression level was highest in proliferative zone and decreased gradually from pre-hypertrophic zone to hypertrophic zone in mouse limbs. With the stimulation of BMP2, the highest expression level of H19 was followed after the peak expression level of Sox9, meanwhile, H19 expression levels were positively corelated with chondrogenic differentiation markers, especially in the late stage of BMP2 stimulation, and negatively corelated with hypertrophic differentiation markers. Our further experiments found that silencing H19 promoted BMP2 triggered hypertrophic differentiation through in vitro and in vivo tests, which indicted the essential role of H19 for maintaining the phenotype of BMP2 induced chondrocytes. In mechanism, we characterized that H19 combined with Runx2 and promoted BMP2 mediated Runx2 phosphorylation. Conclusions: These findings suggested H19 regulates BMP2 induced hypertrophic differentiation of MSCs by promoting the phosphorylation of Runx2.